Factors of Increasing Intention to Use Information Systems - Siswanto; Kusumapradja, Rokiah (IPB University, 2024)
This research is based on information from the IT division regarding non-performance of implementation since the use of HIS at RSU Bhakti Asih began in 2005 until 2022, which has changed three times and none of the implementation achievements for the three HIS have ever reached 100 percent. The aim of this research is to empirically reveal the influence of training and utility on intention to use HIS with work motivation as a mediating variable. This type of research is quantitative with a causality design. The population used is health workers consisting of outpatient nurses, inpatient nurses, emergency room nurses, pharmacy departments, laboratory departments and radiology departments. The sampling technique used proportional sampling, with calculations using the Slovin formula with an error rate of 5 percent, so that the sample size was determined to be 175 respondents. Data collection analysis techniques use survey methods, and data analysis techniques use SEM with the help of the Lisrel program and three box method analysis. The results of the analysis prove that training and utility influence the intention to use HIS with work motivation as a mediator, training influences utility, training and utility influence work motivation and intention to use HIS, and work motivation influences intention to use HIS and is also able to provide positive intervention on the influence training and utility on intentions to use HIS, so that with work motivation, the effectiveness of training and utility will be higher in increasing intentions to use HIS.